Analisis Perkembangan Penanggulangan Pencemaran Udara Yang Disebabkan Oleh Bahan Bakar Fosil - Salsabila, Wardah Nibras; ., Yushardi; ., Sudarti (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Air is a component of life that is very important for the survival of living things. Living creatures need oxygen gas to continue breathing. Clean air is hard to find. This is because the air has been polluted by several substances and particles that damage the air network. There are various forms of air pollution, one of which is air pollution due to fossil fuels. Fossil fuels are often used in motor vehicles and industrial factories. This requires special attention by both the government and society. The purpose of this analysis is to determine the impact caused by air pollution and the countermeasures that have been carried out in Indonesia. The method used is the literature study method. This method refers to the analysis of sources such as books and journals. Health is the main aspect that is the impact of air pollution, followed by the economy. The government has issued several policies as an effort to tackle air pollution in Indonesia.